Environmental hydrology and hydraulics : eco-technological practices for sustainable development - Ghosh, S. N. (Some Nath); Desai, V. R. (Venkappayya Rangappayya), 1960- (Enfield, NH : Science Publishers, 2006)
Water is a precious natural resource, which is crucial to our survival. It needs to be used judiciously in the context of an increasing population not only to sustain essential requirements such as those for drinking and domestic usage, but also for increased food production, industrial usage, power generation, navigational requirements, pisciculture, recreation, landscaping etc. There are many books dealing with hydrology, hydraulics and hydraulic structures, which generally deal with larger problems of development, analysis, design and implementation of water resources. However, there are few books, which deal with small-scale development of water resources consistent with the environmental concerns as well as application of relevant eco-friendly technologies. This book provides both the perspectives.
Eco-hydrological background -- Water uses -- Hydraulic principles and eco-friendly design approach -- Water hazards and their management -- Eco-technological practices for sustainable development.
Includes bibliographical references and index.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Water resources development; Hydraulic engineering -- Environmental aspects; Water conservation; Ecohydrology; Green technology; Electronic books